Enhanced Adaptive Playout Scheduling and Loss Concealment Techniques for Voice over IP Networks - Florencio, Dinei; He, Li-wei (ISCAS 2011, 2011)
Voice over IP (VoIP) is already of commercial quality when traversing corporate, or other high-quality networks. Nevertheless, to make the final bridge to toll quality over standard internet connections, a few problems remains to be solved. These include packet loss, jitter control, and clock drift compensation. Previous research in adaptive playout mechanisms has significantly contributed towards that end. In this paper, we present a novel technique that enhances previous adaptive playout mechanisms, and virtually eliminate late losses. Additionally, enhanced stretching and loss concealment algorithms are also presented. These work in harmony with the proposed technique to alleviate network jitter and any clock drift.